Green topologies and landscapes beyond the land. A 30-years research on green hybridization - Manuel Gausa (Agathón)
New urban metabolisms and their faster anthropic status require new inter-connected environmental systems, able to encourage effective interaction between inter-and endo-urban ‘factories’ and ‘landscapes’, but a new, much more fluid and transversal ‘green’ dimension, aimed at fostering a fertile encounter between nature and the city, eco-structure and infrastructure, technology, topography and topology, interweaving the territory, reinforming its very structural fabrics and above all ‘renaturalising’, through flexible meshes, its diverse and varied pre-existences. New eco-systemic ‘city-architecture-infrastructure-landscape’ strategies are required, but also new types of spatial repertoires with more complex geometries (more flexible, elastic and organic) linked to the dynamics of a changing environment and its multi-scalar manifestations: new topographies, topologies and topomorphies (but also para-topologies) that are more hybrid because, paradoxically, they are more sensitive to nature; approaches favoured by the current eco-technological capacity to work with new responsive materials in which vegetation and all bio-active organisms would combine into new multi-scalar spatial devices, ‘networked environments’, highlighting the shift from a defensive ecology to a proactive ecology and even an increasingly techno-performative ecology.